2009
DOI: 10.1136/thx.2008.103986
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurement of rectus femoris cross-sectional area and the relationship with quadriceps strength in COPD

Abstract: Background: Quadriceps weakness and loss of muscle mass predict mortality in chronic obstructive pulmonary disease (COPD). It was hypothesised that a reduced quadriceps cross-sectional area could be detected by ultrasound in patients with COPD compared with healthy subjects, and that measurements relate to strength and fat-free mass (FFM). Methods: Rectus femoris muscle cross-sectional area (RF CSA ) was measured by ultrasound and whole-body FFM estimated using electrical bioimpedance. Quadriceps strength was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
323
5
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(369 citation statements)
references
References 35 publications
25
323
5
16
Order By: Relevance
“…The strong correlation of USRF CSA with both mid-thigh and rectus femoris CT measurements supports the use of the rectus femoris as a representation of quadriceps bulk and confirms our initial findings in a small cohort of COPD patients [17]. Furthermore, interobserver and inter-occasion agreement for USRF CSA measurement in this study were similar to that for other muscle ultrasound imaging [40].…”
Section: Significance Of the Findingssupporting
confidence: 77%
See 2 more Smart Citations
“…The strong correlation of USRF CSA with both mid-thigh and rectus femoris CT measurements supports the use of the rectus femoris as a representation of quadriceps bulk and confirms our initial findings in a small cohort of COPD patients [17]. Furthermore, interobserver and inter-occasion agreement for USRF CSA measurement in this study were similar to that for other muscle ultrasound imaging [40].…”
Section: Significance Of the Findingssupporting
confidence: 77%
“…Ultrasound rectus femoris cross-sectional area Measurement of quadriceps rectus femoris cross-sectional area was made by ultrasound using a technique previously described by SEYMOUR et al [17]. B-mode ultrasonography was used with an 8-MHz, 7-cm linear array transducer (PLF 805 ST; Toshiba Medical Systems, Crawley, UK).…”
Section: Patients and Study Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Two B-mode ultrasound measures have been reported that quantify wasting (2, 3): (1) combined thickness of the rectus femoris (RF) and vastus intermedius muscles ("muscle layer thickness," henceforth referred to as "thickness") (4, 5); and (2) RF cross-sectional area (RF CSA ), which correlates with lower-limb strength in other clinical circumstances (6). The degree to which either of these ultrasound measures reflect muscle weakness in the critically ill is unclear (7).…”
Section: To the Editormentioning
confidence: 99%
“…Some authors [5,6] have proposed ultrasound assessment of lower limb muscles to quantify the improvements following resistance training. Scanning was performed at the mid-thigh region, and quadriceps mass was assessed by measuring rectus femoris cross-sectional area (RFcsa) and quadriceps muscle thickness (Qt).…”
Section: Introductionmentioning
confidence: 99%